Testing a non linear model of monetary policy reaction function: evidence from Malaysia - Norlin Khalid,; Zulkefly Abdul Karim,; Izzuddin Yussof, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper estimates a nonlinear model of monetary policy reaction function by augmenting the standard Taylor rule equation for the case of Malaysia. M\netary policy reaction function is identified by which the BNM sets the current level ofpolicy rates after observing the current level ofoutput, inflation and exchange rate, and lags ofthesevariables (bachuard looking). (Jsing quarterly time series data set spanningfrom 1991 to 2014, thefindings support the relevance of Taylor rule in which the Bank Negara Malaysia (nNu) sets their policy rates based on both inflation and output growth. In addition, the BNM has also considered the exchange rate in their reactionfunction.